Jurisprudence of the Banda Aceh Syar'iyyah Court in the Determination of Post-Divorce Child Support - Mujibur Rahman; Shabarullah Shabarullah; Ghazal Lianne (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study examines the judicial considerations and implementation of child support arrangements following divorce as stipulated in the Decision of the Mahkamah Syar’iyyah Banda Aceh Number 450/Pdt.G/2023/MS.Bna, as well as the form of legal protection afforded to children’s rights. Using a descriptive qualitative method with a normative juridical approach, this research analyzes relevant statutory regulations, Islamic legal principles, and the court decision as the primary data source. The findings reveal that the judges endorsed the parties’ agreement regarding child custody and financial responsibility, resulting in a shift of the child support burden from the father to the mother. This determination was made on the basis of the child’s best interests, despite the normative rule that places the primary obligation of support on the father according to Article 41 of Law No. 1 of 1974, Article 80 of the Compilation of Islamic Law, and classical fiqh principles. Mahkamah Syar’iyyah adopts a flexible approach in allocating support obligations when justified by mutual agreement and the welfare of the child. Theoretically, this study contributes to strengthening the maqāṣid al-sharī‘ah framework particularly the principle of maslahah al-walad within contemporary family law adjudication. The study underscores the need for continuous evaluation of religious court practices to ensure consistent and effective protection of children’s rights to financial support after divorce.